Police culture: themes and concepts - Cockcroft, Tom (Routledge, 2013)
Acknowledgments -- Introduction -- Organizational and occupational cultures -- Occupational culture and policing -- Police culture : traditional approaches -- Police culture(s) : explaining variation -- Researching police culture -- Managing police culture -- Conclusion -- References